The Use of Demonstration Projects to Advance Criminal Procedure Reform in China - Stutsman, Thomas (Columbia Journal of Asian Law, 2011)
American legal scholars and criminal justice officials widely recognized that bail systems in the United States were deeply flawed in the early 1960s.’ Judges released defendants primarily according to their ability to post bail rather than their risk of fleeing the jurisdiction or committing another offense before trial.’ Poor defendants were more likely to be detained before trial-as well as lose their jobs, be convicted of an offense, and be sentenced to prison as a result of their pretrial detention-simply because they were poor.’ But despite widespread recognition of these injustices, few reforms had been shown to be effective or feasible. In 1961, the Vera Foundation (now the Vera Institute of Justice) initiated the Manhattan Bail Project. A research team, organized by a philanthropist and a magazine editor troubled by the failings of the bail system, collaborated with a criminal court in New York City to test reforms to bail procedures.’ The researchers collected and carefully analyzed data on the effects and feasibility of implementing these reforms.’ They then co-sponsored and presented the results of the project at a conference attended by numerous high-level officials.6 Based in part on the results of the project-the first of its kind in the United States-the federal government and many states passed bail reform laws aimed at increasing the fairness of pretrial release decisions by making them more sensitive to the suspect’s actual risk of fleeing the jurisdiction or committing an offense prior to trial, rather than simply the seriousness of the alleged crime and the suspect’s ability to secure the cash or property necessary to post bail. Forty years later and ten thousand miles away, Chinese legal scholars and criminal justice officials widely recognized coerced confessions as one of the most pressing problems facing the justice system.